1999
DOI: 10.1523/jneurosci.19-13-05301.1999
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Dependent Neuromodulation of Na+Channels by D1-Like Dopamine Receptors in Rat Hippocampal Neurons

Abstract: Activation of D1-like dopamine (DA) receptors reduces peak Na+ current in acutely isolated hippocampal neurons through phosphorylation of the alpha subunit of the Na+ channel by cAMP-dependent protein kinase (PKA). Here we report that neuromodulation of Na+ currents by DA receptors via PKA is voltage-dependent in the range of -110 to -70 mV and is also sensitive to concurrent activation of protein kinase C (PKC). Depolarization enhanced the ability of D1-like DA receptors to reduce peak Na+ currents via the PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 41 publications
3
57
0
1
Order By: Relevance
“…Skeletal and cardiac muscle sodium channels interact directly with the cytoskeletal element syntrophin, which may determine their localization (10). The interaction of brain sodium channels with AKAP15 is required for dopaminergic modulation (11). More recently, the C-terminal polypeptide of rNa v 1.2 (brain type II) was shown to bind calmodulin, suggesting modulation of these channels by Ca 2ϩ (23), and the rNa v 1.2-L1 was shown to interact with synaptotagmin in a Ca 2ϩ -regulated manner (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal and cardiac muscle sodium channels interact directly with the cytoskeletal element syntrophin, which may determine their localization (10). The interaction of brain sodium channels with AKAP15 is required for dopaminergic modulation (11). More recently, the C-terminal polypeptide of rNa v 1.2 (brain type II) was shown to bind calmodulin, suggesting modulation of these channels by Ca 2ϩ (23), and the rNa v 1.2-L1 was shown to interact with synaptotagmin in a Ca 2ϩ -regulated manner (46).…”
Section: Discussionmentioning
confidence: 99%
“…The C terminus of skeletal muscle and cardiac muscle ␣-subunits, SkM1 and SkM2, respectively, bind to syntrophin via their PDZ domain, thus linking these channels to the cortical actin network and extracellular matrix through the association of syntrophin with the dystrophin-associated protein complex (10). Brain ␣-subunits are phosphorylated at specific serine/threonine sites by protein kinase A that is anchored to the ␣-subunit via AKAP15 (11,12). Receptor protein-tyrosine phosphatase (RPTP␤) interacts with brain ␣-subunits via its carbonic anhydrase homology extracellular domain and its intracellular phosphatase domain and phosphorylates tyrosine residues of the channel (13).…”
mentioning
confidence: 99%
“…4), indicating that the I NaT capacity of mPFC neurons taken from both treatment groups is similar in the absence of PKA activity. A key aspect of PKA modulation of I NaT is its voltage dependence (Cantrell et al, 1999;Carr et al, 2003). Cantrell et al (1999) demonstrated in hippocampal neurons and Carr et al (2003) demonstrated in mPFC neurons that PKA-induced inhibition of I NaT is reduced when holding neurons at more hyperpolarized potentials (e.g., Ϫ90 mV).…”
Section: Receptor-mediated Suppression Of I Nat In Mpfc Neurons Imentioning
confidence: 99%
“…It is well established that Na þ channels are under dynamic control of phosphorylation/dephosphorylation Schiffmann et al, 1998), in which calcineurin (CaN), a Ca 2þ / calmodulin-dependent serine/threonine protein phosphatase (also known as protein phosphatase 2B, PP2B), plays a significant role (see Catterall, 1997;Yakel, 1997;Herzig and Neumann, 2000;Greengard, 2001;Shibasaki et al, 2002 for a review). For instance, while cAMP-dependent protein kinase A (PKA) phosphorylates Na þ channels, which leads to a decrease in I Na (Li et al, 1992;Cantrell et al, 1999;Smith and Goldin, 1997), CaN dephosphorylates specific serine sites in the intracellular loop of type II-Aa subunit of Na þ channels (Murphy et al, 1993) and enhances I Na (Hu et al, 2005). Although PKA-activated p-Thr.34-DARPP-32 reduces I Na , CaN inhibits this action of p-Thr.34-DARPP-32 Schiffmann et al, 1998).…”
Section: Introductionmentioning
confidence: 99%